PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP PENINGKATAN PENGUASAAN MUFRODAT (KOSA KATA) PEMBELAJARAN BAHASA ARAB PESERTA DIDIK KELAS VII MTS MATHLA’UL ANWAR CEMPLANG TAHUN PELAJARAN 2022/2023 - Dwita, Diana (Program Studi Pendidikan Bahasa Arab, 2023)
Teachers are not only required to be able to teach in class. However, another important qualification is being able to master learning perspectives and, using media is one of the factors that also determines the success of learning. This research was conducted to see whether there was an effect of using Video Animation Media on increasing vocabulary mastery in learning Arabic at MTs Mathlaul Anwar Cemplang. This research is a quantitative study using the type of Quasi Experimental one group Pretest Posttest design which is useful for measuring the comparison of results before being given treatment and after being given treatment. From the table of the paired sample t-test conducted on the results of the pre- test and post-test values, the values obtained are t hitung (10,949) > t table (1.668) This means that there is a significant increase in mufrodat mastery after the treatment is given. it can be concluded that the use of animated video media has an effect on the mastery of mufrodat in class VII MTs students Mathla'ul Anwar Cemplang for the 2022/2023 Academic Year